Exploring protein - protein interaction in cell physiology by reviewing the role of dynein-dynactin interaction as a representative example - Neelabh DATTA (Studia Universitatis Babeș-Bolyai. Biologia)
Protein-protein interactions are essential for the normal function of cells and are involved in various cellular processes. These interactions can occur through a variety of mechanisms, including hydrogen bonding, ionic interactions, and hydrophobic interactions. Changes in protein-protein interactions can alter the normal function of the cell and lead to various diseases. Understanding protein-protein interactions is important for the development of therapeutic approaches targeting these interactions for the treatment of diseases. In this article, I will discuss the role of protein-protein interactions in normal cellular function, the consequences of changes in these interactions, and the importance and significance of understanding these interactions by using the example of dynein-dynactin.